Financial and relationship satisfaction as a function of harsh start-up and shared goals and values - Archuleta, Kristy L.; Grable, John E.; Britt, Sonya L. (My University, 2013)
A path model was developed to test hypothesized associations among financial satisfaction, harsh start-up, shared goals and values, and relationship satisfaction. It was noted that a partner’s perceived financial satisfaction was directly associated with engaging less in harsh start-up discussions and sharing goals and values with the other partner. Harsh start-up discussions were directly associated with having fewer shared goals and values and decreased relationship satisfaction. The association between financial satisfaction and relationship satisfaction in the model was mediated by harsh start-up and shared goals and values. Implications for both practitioners and researchers are discussed.
Keywords: Financial satisfaction; Harsh start-up; Relationship satisfaction; Shared goals and values